Active, Small-Scale, Periglacial Features on the South Coast of Newfoundland - Leckie, D.; McCann, S. (Géographie physique et Quaternaire, 1982)
ABSTRACTSmall-scale, patterned ground is currently forming on the south coast of Newfoundland. Small, sorted circles and stripes form in the vicinity of the coast under the influence of marine climate with numerous, short duration, freeze-thaw cycles, high humidity, abundant rainfall and a thin snow cover throughout the winter, inland, no more than 15 to 25 km from the coast, the marine influence has decreased sufficiently that the patterned ground is no longer forming.